Y-CHROMOSOME MICRODISSECTION AND Y-LINKED GENES IDENTIFICATION OF THE GIANT PANDA (AILUROPODA MELANOLEUCA) - Y. X. Chen; C. J. Zeng; S. G. Fang (Journal of Animal and Plant Sciences, 2022)
The Y chromosome plays an important role in the sexual reproduction of many species because it contains sex-determining genes and male reproductive factors and the Y chromosome has only been sequenced in a few mammalian species. Y chromosome has been study in several fields, such as spermatogenesis, male development and sex chromosome evolution. The giant panda (Ailuropoda melanoleuca) is an endangered species in China. Male giant pandas have reproductive defects such as low natural mating rate, poor sperm quality, and infertility that inhibit population growth. More information is needed on the genetics of giant panda reproduction in order to understand their biological characteristics. The Y chromosome data of the giant panda are now unavailable, though a draft genome of this species has been sequenced. Thus, in the present study, we separated single Y chromosomes of male giant panda, sequenced using high-throughput sequencing after whole genome amplification. Finally, two genes, ZFY and TSPY1, on Y chromosome and related to male fertility were annotated. This study is a supplement of giant panda genetic data.
Keywords: Giant panda; reproduction; sex chromosome; whole genome amplification; Y-linked genes